Academic Supervision Leadership Model: Transition from Administrative Compliance to Coaching-Based Development - Abdullah Abdullah; Djam'an Satori; Sururi Sururi; Suryadi Suryadi; Maria Ulfa (Universitas Negeri Malang, 2025)
Abstract: Academic supervision represents a critical leadership function for enhancing teaching quality and student learning outcomes. This study employs grounded theory methodology to investigate academic supervision practices in three Madrasah Aliyah Negeri (MAN) schools in Bireuen Regency, Aceh. Through in-depth semi-structured interviews with three school principals and data analysis using ATLAS.ti version 24 with a structured Q&A framework (12 identical questions × 3 informants = 36 unique codes), this research identifies three distinct supervision models along a developmental continuum: (1) administrative mentoring—focused on procedural compliance with minimal impact on teacher development; (2) professional mentoring—demonstrating intermediate mentoring approach with moderate effectiveness; and (3) continuous mentoring—embodying systematic development mechanisms with substantial impact on learning quality. Findings reveal significant gaps between national policy frameworks and school-level practice, alongside structural, human, and material barriers limiting coaching-based supervision implementation. This research proposes a transformative supervision model integrating continuous coaching, reflective practice, collaborative problem-solving, and data-driven decision-making. Contributions include understanding contextual barriers to academic supervision effectiveness in Indonesian Islamic education institutions and practical recommendations for instructional leadership development programs feasible within resource-constrained contexts. Keywords: academic supervision, instructional leadership, teacher development, continuous coaching, learning quality, grounded theory